Formação continuada de professores do ensino médio: dispositivos de escuta e análise das práticas profissionais - Dantas, Angélica Guedes (2018)
Faced with a crisis that has stricken the educational context, where the prevailing educational landscape has prevented teachers from professionally constituting themselves in a critical and reflective manner, impacting their actions in the classroom, leading them to illness, this thesis aims to investigate and assess the ways in which teachers develop prevention and intervention strategies to deal with suffering, school failure and violence at schools. It was conducted through a psychoanalytically-oriented interventive research, supported by listening devices and the analysis of professional practices. Eight teachers from a Public High School in the Federal District participated in the research, where they generated data through group conversations. The analysis was carried out through the elaboration of axes of meaning, which could favor the apprehension of the senses and meanings attributed by teachers to their professional practices. Those axes of meaning, chosen for the analysis and problematization of results, were: Public Policy and School Management; Teacher Suffering and its Implications in Pedagogical Practice. The conclusion points to two possible paths: that of prevention, through the formulation of educationally-oriented public policies, and that of intervention, which takes place in practice and helps teachers cope with the daily challenges imposed by their profession. On the one hand, different discourses have highlighted the dilemmas experienced by subjects in their daily school lives: the anguish, the resentments (with the profession, students, families, colleagues and superiors, even with the government and the public policies implemented in the field of education) and the psychic suffering itself. They have also highlighted the permanence of the group in a defensive and resisting position, where one can spot different attempts at remaining away from subjectivity. On the other hand, the discourses have stressed an amalgam between the development of subjectivities and the institutional and social dynamics geared towards the formulation and implementation of public policies in the field of education, notably in the current political moment. Among the obstacles faced to carry out this work, one can point to the lack of time (number of sessions undertaken, the duration of the intervention and the need to handle the end goal more carefully); the absence of an addressed demand and the resistance of the group (difficulty of implication), given the enjoyment experienced by remaining in a victimizing and complaining position. The lurking possibility that psychoanalysis could contribute to the field of education points to the urgency of a reflective perspective with regard to educational practices. It also points to the need for those who formulate public policies in the field of education to think about educational practices as tools to train the subject, all while not losing sight of the subjectivity of those willing to become teachers.